TINJAUAN PUSTAKA: DAMPAK BODY IMAGE DAN KEMATANGAN EMOSI PADA PSYCHOLOGICAL WELL-BEING MASA DEWASA AWAL - Khairunnisa, Kamila Putri; Yudatama, Pandu; Suparmi, Suparmi (Jendela Inovasi Daerah, 2025)
Negative body image can have a negative impact on an individual's psychological well-being. However, good emotional maturity can act as a protective factor in reducing these negative impacts. This research aims to examine the relationship between body image, emotional maturity, and psychological well-being in early adult individuals. The method used is a literature review by collecting relevant scientific articles published in the last five years obtained through the Publish or Perish application. Of the 200 articles accessed via Google Scholar, 38 articles met the criteria. The research results show that poor body image is correlated with low emotional maturity and has a significant negative impact on psychological well-being. On the other hand, high emotional maturity can reduce the negative impact of body image on psychological well-being. These findings emphasize the importance of developing emotional maturity as a strategy to improve psychological well-being in young adults who have negative self-perceptions.